Design Application of User Management to Support Application of Information System - Sutedi Sutedi (Jurnal Ilmiah ESAI, 2013)
Today many institutions are increasingly aware of the benefits and positive effects of the existence of information systems are built, and implemented as an optimization effort of information technology to support existing business processes. Information system is built in an institution/agency should be able to apply the rules that apply correct management.Â  In some cases the application of information systems, users management problem often neglected and not well-designed so that potential deviations that can be harmful the institution. User management and sharing permissions within the system should be limited and well handled to minimize the occurrence of irregularities, in addition to data security needs to be done also periodic backup and continuous data.Keywords: user management, access rights, data backup.